ANALYTICS AND KINETICS OF CRYSTALLIZATION OF MAGNESIUM SULPHATE FROM SEA BITTERN, THROUGH SUPERSATURATION - Azmat, Farzana; Mahmood, Syed Naeem; uddin, Nayeem (Biological Sciences - PJSIR, 2004)
Experimental part of the studies consist of change in concentration of magnesium sulphate against time of its crystallization from sea bittern during chilling. The said data is represented by characteristic straight lines, the slopes(s) of which give the numerical value of kinetics of reaction (Kinetic constant) suggesting that the reaction is of zero order. It is observed that in case of normal bittern the kinetic constant is influenced by the % magnesium sulphate which in turn depends on quality of raw material/weather conditions. Nevertheless, in case of any treatment such as heating and reconstitution of sea bittern, the kinetics constant indicated to depend on the ratio of magnesium sulphate to magnesium chloride. Statistically, the data found to be normally distributed, consistent and free from systematic errors. The calculated values of (i) intercepts have been observed to be very close to actual values. In case of verification factor, the change in calculated values found to be +8% to -11% of ideal values. The theoretical portion comprises of comprehensive treatment of energy balance/overall energy balance equations(s), their transformation to different standard straight lines consisting of bivariates, namely concentration/temperature, concentration/time and temperature/time. Subsequent manipulated of the intercepts/slopes of the lines led to derive important relationships such as heat of crystallization and overall heat requirement of the process. Further, the significance of the parameters/terminology involved in the process, have also been appropriately elaborated. Furthermore, the relationship amongst the slopes of three combinations of variables has led to conceive a new term being called ‘verification factor’, which under ideal conditions should be unity and the departure from which would be the indication of different types of errors.